Homework Help

Use the exponent rules to simplify `(a^2*a^-9)/(a^-3)`, leaving exponents as positive...

studentaccount's profile pic

Posted via web

dislike 2 like

Use the exponent rules to simplify `(a^2*a^-9)/(a^-3)`, leaving exponents as positive values, and fractions in lowest terms.

1 Answer | Add Yours

justaguide's profile pic

Posted (Answer #1)

dislike 2 like

The expression `(a^2*a^-9)/(a^-3)` has to be simplified.

`(a^2*a^-9)/(a^-3)`

=> `a^(2 - 9)/a^-3`

=> `a^(-7+3)`

=> `a^-4`

=> `1/a^4`

The expression `(a^2*a^-9)/(a^-3) = 1/a^4`

Join to answer this question

Join a community of thousands of dedicated teachers and students.

Join eNotes